IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG KAKI LIMA (PKL) DI KECAMATAN PATI, KABUPATEN PATI - Nur Fadhilah Aniq; Margaretha Suryaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The purpose of this study was to look at the implementation of the street vendor arrangement policy in Kecamatan Pati, as well as the determinants of the course of implementation. This study used qualitative research methods. The results showed that the factors supporting the implementation of the Street Vendor (PKL) arrangement policy were social conditions, namely the community agreed and enthusiastic about the Government's policy regarding the arrangement of Street Vendors (PKL) in Pati Regency. For political conditions, there is support, namely in the form of assistance in submitting cooperation with Perhutani in relation to leasing land for relocation planning in 2019. Resource factors and economic conditions also become obstacles in the implementation process, human resources or in this case the team assigned to the socialization process and law enforcement is actually enough, but because there are additional personnel and some of them are still carrying out training, the implementation process cannot run optimally. From the economic conditions there are still infrastructure facilities, namely the addition of vehicles for the mobilization of officers, which have not been approved by the Government due to limited funds. Suggestions, namely relocation for Street Vendors (PKL), will soon be realized so that Street Vendors (PKL) can sell, so that the presence of Street Vendors (PKL) becomes more organized and the environment becomes safe and clean. Socialization is carried out as much as possible it must be evenly distributed so that the Street Vendors (PKL) will also know about the regulations, while for the Street Vendors (PKL), immediately make a TDU (Business Register) so that their merchandise is registered with the government